Electrodeposited MnO2- Carbon Cloth Supercapacitor Electrode Material for High Power Applications - Selvaraj, Shanthi; Hayakawa, Yasuhiro; Ponnusamy, S; Ikeda, Hiroya; Chellamuthu, Muthamizhchelvan (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Carbon cloth is a promising new material for the electrodes of supercapacitors, owing to their high surface area, flexibility, high conductivity with chemical stability. In this work, MnO2 was electrodeposited on a commercially available post treated carbon cloth. The MnO2 deposited carbon cloth was examined using HRSEM, which reveals the formation of nanosized irregular structure of MnO2 over the carbon cloth. Electrochemical study was performed which revealed the specific capacitance of 483 Fg–1 at a scan rate of 10mVs–1. The fabricated device exhibited good electrochemical performance with energy density of 22WKg–1 at a power density 330KWKg–1. The results were convincing to use this material for high power applications.